Desenvolvimento de aplicativo para dispositivo móvel orientado para a gestão dos custos de projetos de recomposição de áreas degradadas e alteradas - Boldrin, Jeferson Lamartine (2022)
The innovation research presents the development of an instrument that helps professionals in the restoration of degraded and/or altered areas. This innovation occurred through the adaptation of the methodology of IBAMA's Technical Note 40/2019, which estimates the costs of various management techniques in Brazilian biomes, moving from a static file in "PDF" format to a dynamic system oriented to mobile devices. To characterize the application, the following parameters were considered: Mobility, Accessibility, Interactivity and Relevance, with the goal of reducing risks in estimating the costs of a PRADA. These parameters guided the construction of an application for smartphones with the Andriod system, agile, easy to use that allows professionals to equalize the costs of their projects with a greater degree of assertiveness. The cost spreadsheet of environmental restoration techniques by biome was converted, which previously only existed in PDF format, to an application used on mobile devices using the Kodular platform. The information obtained in the field is saved in the device and later allocated in a database where the user can have access. The application, based on the parameters, provides a list of the techniques available for the chosen biome, which, recorded for a specific budget number, generates a list of the chosen services with their values and the total cost. It is expected that the research will collaborate with the projects for the recovery of degraded areas, so that they are more assertive, in terms of projecting the costs of the management actions established, contributing to the reduction of environmental liabilities, as well as complying with the rules of the Forest Code.